Risk Analysis of Delay in Ship Repair KM Binaiya with Bayesian Network Method - Intan Baroroh; Galuh Valent Setiawan; Ali Azhar; Didik Hardianto; Ahmad Basuki Widodo (International Journal of Marine Engineering Innovation and Research, 2023)
Ship repair is a project that is short in process so that time is an important element in its completion parameters. Delay is something that can happen to a job. A job experiencing delays must have a cause that affects the work. Causes of delay in the case of ship repair are poor time management, less skilled human resources, the addition or development of work. But whatever the obstacles, shipyards are still required to complete the ship repair process in a timely manner. Seeing this problem, this research was conducted to provide input in connection with the strategies used by PT XYZ in overcoming the delay factor in the repair of the KM Binaiya ship. In the research to support this thesis, the Bayesian Networks Method is used to analyze the factors that cause delays in ship repairs. After risk identification using the Bayesian networks method. The highest risk is replete activities as minor categorized, where the caused tank cleaning work related to hazardous waste, which must be cleaned to be safe for hot work with a risk score of 0.108. The second cause is installation of scaffolding for replete work facilities at height with a risk score of 0.054.